PENGARUH CORPORATE GOVERNANCE, BUDAYA PERUSAHAAN DAN KESEMPATAN PERTUMBUHAN TERHADAP KINERJA PERUSAHAAN PADA HOTEL BERBINTANG DI BALI - Pradnyana Putra, Ida Bagus Ega; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
Corporate governance is becoming a very important issue with the monetary crisis ever to hit Asian countries, associated with the emergence of various claims against the company management in a professional and transparent. Weak corporate Governace often cited as one cause of the financial crisis in countries Asia. This research is aimed to know how to influence corporate governance, corporate culture and growth opportunities to the company's performance on a five-star hotel in Bali. The data used in this study are primary data by distributing 286 questionnaires. Data analysis techniques used in this research is multiple linear regression. Based on the analysis, it is known that the variable corporate governance and company's culture positive effect on company performance, while the growth opportunities not affect the company's performance.
Keywords: corporate governance, corporate culture, growth opportunities, company performance